Genre in archaic and classical Greek poetry : theories and models - Foster, Margaret, 1977-; Kurke, Leslie,; Weiss, Naomi A., 1982- (Mnemosyne, Supplements;, 2020)
Genre in Archaic and Classical Greek Poetry foregrounds innovative approaches to the question of genre, what it means, and how to think about it for ancient Greek poetry and performance. Embracing multiple definitions of genre and lyric, the volume pushes beyond current dominant trends within the field of Classics to engage with a variety of other disciplines, theories, and models. Eleven papers by leading scholars of ancient Greek culture cover a wide range of media, from Sappho's songs to elegiac inscriptions to classical tragedy. Collectively, they develop a more holistic understanding of the concept of lyric genre, its relevance to the study of ancient texts, and its relation to subsequent ideas about lyric.